The impact of vascular calcification on ambulatory and central aortic blood pressure in a South African dwelling dialysis population : a clinical, radiological and pathophysiological study of vascular health in a young prevalent dialysis population in a developing country - Freercks, Robert Jeremy (Department of Paediatrics and Child Health, 2015)
Includes abstract.